Highly effective thieno[2, 3-b]indole-diketopyrrolopyrrole near-infrared photosensitizer for photodynamic/photothermal dual mode therapy. (December 2017) - Yang, Jing; Cai, Yu; Zhou, Yanxiang; Zhang, Caixia; Liang, Pingping; Zhao, Baomin; Shao, Jinjun; Fu, Nina; Huang, Wei; Dong, Xiaochen
Abstract: Synthesis of photodynamic and photothermal agents with absorption in the near-infrared (NIR) region and featuring excellent photostability, high singlet oxygen generation efficiency, good photothermal conversion efficiency, and good biocompatibility is necessary for the application of photodynamic therapy (PDT) and phtothermal therapy (PTT). Three NIR absorption compounds based on thieno[2, 3- b ]indole (TI) and diketopyrrolopyrrole (DPP) were designed and synthesized. Their UV-vis-NIR absorption, photoluminescence, electronic distribution, energy levels and thermally induced phase transitions have been carefully determined. As structural analogues, onlyDPP-TI possesses excellent singlet oxygen quantum yield ( 1 O2, ΦΔ  = 48.5%), which displays effective photothermal conversion efficiency (η = 15.8%) as nanoparticles in water. The potential ofDPP-TI nanoparticles as fluorescence imaging therapeutic agent for synergetic PDT and PTT in vitro using only one wavelength light were explored preliminarily. Graphical abstract: Highlights: D-A-D type NIR photosensitizer consists of TI and DPP unit. Optical and electrochemical properties of resultant compounds were compared. Only one structural analogue displays excellent 1 O2 generation efficiency. DPP-TI NPs were prepared and used as NIR fluorescence imaging probe. DPP-TI NPs exhibited excellent PDT and PTT efficiency.